Hubungan antara Self-Esteem dengan Kecenderungan Smartphone Addiction pada Remaja Akhir - Putri Haz; Halimah, Lilim (Bandung Conference Series: Psychology Science, 2024)
Abstract. Self-esteem is an important factor that influences how adolescents interact with their environment and how they make social adjustments based on their self-assessment. Individuals -with low self-esteem often experience loneliness, anxiety, and a sense of rejection from their environment, which can impact smartphone use. This study aimed to explore the relationship between self-esteem and smartphone addiction in late adolescents. Quantitative methods were implemented in this study with a correlational approach, this study involved 198 late adolescents who live in Bandung, who were selected by purposive sampling. The measurement tools used include the Smartphone Addiction Scale Short Version (SAS-SV) developed by Kwon, Kim, Cho, and Yang (2013) and adapted by Cindy Chias, Elmeida Effendy, and Mustafa Mahmud (2019), and the Rosenberg Self-Esteem Scale (RSE) adapted by Nelan Maroqi in 2018. Data analysis was conducted using Pearson Correlation. The results showed a correlation coefficient (r) of 0.986 with a P value <0.001, which indicates a very strong relationship between self-esteem and smartphone addiction. The results of this study suggest that adolescents with high self-esteem are more likely to experience smartphone addiction. Therefore, it is important for adolescent smartphone users with high self-esteem to understand this risk and implement strategies to use their smartphones more wisely. Abstrak. Self-esteem merupakan faktor penting yang memengaruhi bagaimana remaja berinteraksi dengan lingkungannya dan bagaimana mereka melakukan penyesuaian sosial berlandaskan penilaian pada dirinya sendiri. Individu dengan self-esteem yang rendah sering mengalami kesepian, kecemasan, dan rasa penolakan dari lingkungannya, yang bisa berimbas pada penggunaan smartphone. Penelitian ini bermaksud untuk mengeksplorasi hubungan antara self-esteem dan smartphone addiction pada remaja akhir. Metode kuantitatif diimplementasikan dalam studi ini dengan pendekatan korelasional, penelitian ini melibatkan 198 remaja akhir yang berdomisili di Bandung, yang dipilih secara purposive sampling. Alat ukur yang dipakai antara lain Smartphone Addiction Scale Short Version (SAS-SV) yang dikembangkan oleh Kwon, Kim, Cho, dan Yang (2013) dan diadaptasi oleh Cindy Chias, Elmeida Effendy, dan Mustafa Mahmud (2019), serta Rosenberg Self-Esteem Scale (RSE) yang diadaptasi oleh Nelan Maroqi pada tahun 2018. Analisis data dilakukan dengan menggunakan Pearson Correlation. Hasil penelitian memperlihatkan nilai r = 0,986 dengan nilai P <0.001, memperlihatkan hubungan yang sangat kuat antara self-esteem dan smartphone addiction. Temuan ini mengindikasikan bahwa remaja dengan self-esteem yang tinggi lebih besar kecenderungan untuk mengalami smartphone addiction. Bagi remaja pengguna smartphone yang memiliki self-esteem yang tinggi perlu memamhami dan perlu strategi untuk memanfaatkan smartphone dengan lebih bijak.